Development of Learning Media Based on Gamification of Hijayyah Letters in Elementary Schools - Mahardikha, Sekhar Khairunnisa; Yusuf, Munawir; Musdad, Akhmad Arif (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Post-pandemic learning activities, especially in elementary schools, have been carried out face-to-face learning. Before all face-to-face learning activities are implemented, all parties must have implemented limited face-to-face learning. Limited face-to-face learning is a learning process that is carried out face-to-face between students and a limited number of school educators/teachers. Limited face-to-face meetings are carried out with 2 sessions, namely the morning session and afternoon session with 1 class in each session ranging from 10-16 students by implementing students and teachers wearing masks while learning takes place, seating between students is provided distance by emptying 1 table, before and after learning takes place students are required to use hand sanitizers. This study aims to produce a gamification-based learning media that can be used as an independent learning medium so that students can learn without being assisted by anyone and this media can be played anytime and anywhere. The research model used is the ADDIE model. The ADDIE development model consists of five stages including analysis, design, development, implementation, and evaluation. This application was tested on 19 grade 1st elementary school students. This research was conducted from January to October 2022. The results showed that this learning media was of interest to Grade 1st elementary school students and received a very good response.